The first industrialization in Navarre: The ferrerías in the Later Middle Age - Mugueta Moreno , Iñigo (Huarte de San Juan. Geografía e Historia, 2009)
The establishment of the first iron workshops in the Cantabrian-Pyrenean strip seems to date back to the last third part of the 13th century. There are numerous evidences of industrial and mining settlements dated from this period along this wide geographical area. The aim of this work is to analyze the development of the iron industry in Navarre, to locate some of the early iron workshops, and to meet some of the social and economic conflicts that arose in consequence of the new economic activities. In this way, we will go through two classic debates in historiography: first, the assessment of the importance of technological innovation for economic and social development and secondly, the distribution of rights and powers on the mountain and the subsurface. We will analyze the first documents of the Comptos section of the Archivo General de Navarra (in particular the Libros de Comptos or account books) and in the last part of the work, a lawsuit of the 15th century motivated by the iron exploitation of Mount Arano.